Faktor â Faktor yang Mempengaruhi Kepuasan Kerja (Studi pada Karyawan Sekolah Tinggi Ilmu FarmasiâYAYASAN PHARMASIâ Semarang) - Melani, Titis; ., Suhaji (Jurnal Kajian Akuntansi dan Bisnis, 2012)
The purpose of this study was to determine the influence of financialfactors, physical factors, social factors and psychological factors on employeesatisfaction of Pharmacy school